COVID-19 infection and severe clinical outcomes in patients with kidney disease by vaccination status: a nationwide cohort study in Korea - Jieun Woo; Ahhyung Choi; Jaehun Jung; Ju-Young Shin (Epidemiology and Health)
OBJECTIVES Patients with kidney disease have been prioritized for coronavirus disease 2019 (COVID-19) vaccination due to their susceptibility to COVID-19 infection. However, little evidence exists regarding these patients’ vulnerability to COVID-19 post-vaccination. Thus, we evaluated the risk of COVID-19 in patients with kidney disease compared to individuals without kidney disease according to vaccination status. METHODS A retrospective cohort study was conducted using the Korean nationwide COVID-19 registry linked with National Health Insurance Service claims data (2018-2021). Among individuals aged 12 years or older, 2 separate cohorts were constructed: a COVID-19-vaccinated cohort and an unvaccinated cohort. Within each cohort, the risk of COVID-19 infection and all-cause mortality, hospitalization, and emergency room visits within 30 days of COVID-19 infection were compared between patients with and without kidney disease. To adjust for potential confounding, we used propensity score matching. Hazard ratios (HRs) for each outcome were estimated using a Cox proportional hazard model. RESULTS We identified 785,390 and 836,490 individuals in the vaccinated and unvaccinated cohorts, respectively. Compared to patients without kidney disease, patients with kidney disease were at a higher risk of COVID-19 infection in both the vaccinated cohort (HR, 1.08; 95% confidence interval [CI], 1.02 to 1.16) and the unvaccinated cohort (HR, 1.09; 95% CI, 0.99 to 1.20). Likewise, patients with kidney disease generally were at higher risk for severe clinical outcomes within 30 days of COVID-19 infection. Subgroup and sensitivity analyses showed generally consistent results. CONCLUSIONS Our study observed excess risk of COVID-19 in patients with kidney disease, highlighting the importance of ongoing attention to these patients even post-vaccination.